Comportamento fenológico da liana Pyrostegia venusta (Ker Gawl.) Miers (Bignoniaceae) em área de cerradão na Estação Ecológica de Assis, SP. - Rossatto, Davi Rodrigo [UNESP] (2011)
Brazilian cerrado is characterized by an evident seasonality with distinct dry and wet seasons. Pyrostegia venusta is a common vine found in different physiognomies of the Cerrado. The species may present characteristics that allow its adjustment to the seasonal cycles. The phenology of vegetative and reproductive events was studied for this species in 2004 and 2005. The objective was to verify which climatic factors determine the phenological patterns observed in the species. Flowering was inversely related to mean temperatures and to the length of the day, while fruiting was inversely related to the photoperiod and directly related to the mean wind velocity. Seed dispersal was directly related to wind speed. As a consequence, flowering occurred at the end of the rainy season, close to the winter, and was prolonged until the end of the dry season. Fruiting and fruit maturation occurred during the dry period, with the seeds being dispersed at the end of this period. The seed dispersal at the end of the dry season, common to other anemochoric species of cerrado, allows a rapid germination at the beginning of the wet season, favoring the species propagation in this environment.